Time trends in ophthalmia neonatorum and dacryocystitis of the newborn in England, 2000–2011: database study. (15th December 2014) - Dharmasena, Aruna; Hall, Nick; Goldacre, Raph; Goldacre, Michael J
Abstract : Aims: To investigate English national trends in ophthalmia neonatorum and dacryocystitis (ON) of the newborn and the completeness of statutory notification of this serious infection. Design: Analysis of hospital episode statistics (HES) from 2000 to 2011. Materials and methods: Using linked HES, numbers of neonates hospitalised with ON were identified from 2000 to 2011. The numbers of hospitalised cases were compared with numbers of statutory notifications for ON published by the Notifications of Infectious Diseases (NOIDS). Results: The national incidence rate of hospitalised cases showed a gradual decline from 464 (95% CI 447 to 482) per 100 000 live births in 2000 to 216 (204 to 228) per 100 000 live births in 2005. It then gradually increased to 471 (455 to 487) per 100 000 live births in 2010, but dropped to 257 (245 to 269) per 100 000 in 2011. From 2000 to 2009, when NOIDS data were available, the NOIDS data showed only 1006 cases compared with 20 505 cases in HES, and thus the notification system captured only about 1 case in 20. Conclusions: As shown by hospital statistics, there were marked cyclical fluctuations in ON over the study period. The annual figures for ON reported during the study period, under statutory health protection regulations, underestimated the actual occurrence of this disease by a very substantial amount. Linked hospital data should be used routinely to monitor the national incidence of ON.